Peran Pendidikan Agama Islam dalam Membentuk Karakter Bangsa - Arlina, Arlina; Lestari, Ayu; Putri, Aliyah; Rambe, Ardiansyah; Elsil, Elda Arzetin; Jamilah, Jamilah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the role of Islamic religious education in shaping the nation's character. The study uses a qualitative research method with a literature study, which answers existing problems by reviewing relevant literature to provide solutions. The results show that religious education is an irreplaceable fundamental support in character formation, because religion contains noble values of absolute goodness and truth. These noble values, such as honesty and trustworthiness, will give birth to excellent character in everyday behavior. Islamic religious education is a continuation of the role of religion that not only teaches ritual actions such as prayer and reciting prayers, but more than that, it also shapes the overall behavior of humans in order to obtain the pleasure of Allah SWT. Islamic religious education plays a significant role in shaping the character or behavior of students. Basically, the learning of Islamic religious education is directed towards shaping the character of the students. Through religious education, it is hoped that students will know, understand, and practice character values in daily life, so that they will become students with excellent character.